Neurooncology: 2022 update - Wesseling, Pieter; Rozowsky, Jacob S. (Free Neuropathology, 2022)
Abstract This ‘Neurooncology: 2022 update’ presents topics that were selected by the authors as top ten discoveries published in 2021 in the broader field of neurooncological pathology. This time, the spectrum of topics includes: papers with a direct impact on daily diagnostic practice of CNS tumors in general and with information on how to improve grading of meningiomas; studies shedding new light on the oncogenesis of gliomas (in particular ‘optic gliomas’ and H3-mutant gliomas); several ‘multi-omic’ investigations unraveling the intra-tumoral heterogeneity of especially glioblastomas further; a study indicating the potential of ‘repurposing’ Prozac®; for the treatment of glioblastomas; liquid biopsy using CSF for assessment of residual medulloblastoma. In the last part of this review some other papers are mentioned that didn’t make it to this (quite subjective) top ten list.